Highly degraded RNA can still provide molecular information: An in vitro approach. Issue 5 (3rd February 2020) - Fattorini, Paolo; Bonin, Serena; Marrubini, Giorgio; Bertoglio, Barbara; Grignani, Pierangela; Recchia, Elisa; Pitacco, Paola; Zupanič Pajnič, Irena; Sorçaburu‐Ciglieri, Solange; Previderè, Carlo
Abstract: The long‐term survival of RNA in postmortem tissues is a tricky topic. Many aged/forensic specimens show, in fact, high rates of null/inconclusive PCR‐based results, while reliable outcomes were sometimes achieved from archaeological samples. On the other hand, several data show that the RNA is a molecule that survives even to several physical–chemical stresses. In the present study, a simple protocol, which was already developed for the prolonged hydrolysis of DNA, was applied to a RNA sample extracted from blood. This protocol is based on the heat‐mediated (70°C) hydrolysis for up to 36 h using ultrapure water and di‐ethyl‐pyro‐carbonate‐water as hydrolysis medium. Measurable levels of depurination were not found even if microfluidic devices showed a progressive pattern of degradation. The reverse transcription/quantitative PCR analysis of two (60 bp long) housekeeping targets (glyceraldehyde‐3‐phosphate dehydrogenase and porphobilinogen deaminase) showed that the percentage of amplifiable target (%AT) decreased in relation to the duration of the damaging treatment ( r 2 > 0.973). The comparison of the %AT in the degraded RNA and in the DNA samples that underwent the same damaging treatment showed that the %AT is always higher in RNA, reaching up to three orders of magnitude. Lastly, even the end‐point PCR of blood‐specific markers gave reliable results, which is in agreement with the body fluid origin of the sample. In conclusion, all the PCR‐based results show that RNA maintains the ability to be retro‐transcribed in short cDNA fragments even after 36 h of incubation at 70°C in mildly acidic buffers. It is therefore likely that the long‐term survival of RNA samples depends mainly on the protection against RNAase attacks rather than on environmental factors (such as humidity and acidity) that are instead of great importance for the stability of DNA. As a final remark, our results suggest that the RNA analysis can be successfully performed even when DNA profiling failed.